Causal and preventive interdependence. Elementary principles. - Miettinen, O. S. (Scandinavian Journal of Work, Environment & Health, 1982)
"Synergism" of two factors in the causation or prevention of an all-or-none event means the existence of instances in which both factors are needed for the effect, while "antagonism" means that at least one can block the solo effect of the other. The manifestation of such interdependences--or of their complement, independence--in terms of event rates is complicated by the correlation of the susceptibilities to the two factors. Thus, given the risk difference (RD) values representing the solo effects, the RD corresponding to the joint exposure has a range consistent with independence so that independence cannot be inferred even from very ample data without knowledge of the degree of correlatedness of the susceptibilities. The definition of this range is closely analogous for causal and preventive factors, respectively. However, when knowledge about interdependence is used in inference about the factors' interrelation in the mechanisms for the effect, sharp distinctions may have to be made between causal and preventive factors. In each case, the interdependence is a result of the interrelation of the actions of the two factors and/or interaction between them. Operational decisions, having to do with the wisdom of the joint exposure, can be guided by knowledge about the interdependence of the factors; however, knowledge of the risks corresponding to the various exposures is a sufficient guide, without any need for inferences about causal or preventive interdependence.